Crop diversification as a cornerstone for sustainable agroecosystems: tackling biodiversity loss and global food system challenges - Sandeep Gawdiya; Ramandeep Kumar Sharma; Harphool Singh; Dinesh Kumar (Discover Applied Sciences)
Abstract Crop diversification and its associated practices support natural agroecosystem processes in local, diverse agricultural systems. The widespread appraisal of crop diversification is a fundamental alternative to simplified production systems for enhancing biodiversity in agricultural landscapes. Despite substantial evidence of crop diversification benefits for agroecology, the adoption of these practices lags behind. Despite strong scientific evidence of the benefits, the adoption of these practices remains significantly slower than necessary to address ecological and societal needs. Its adoption largely depends on farmers attitudes, intentions, perceived motivations, governance policies, incentives, and market acceptance. In contrast, successful agronomic interventions require redirecting subsidies toward incentives that promote biodiversity, achieve sustained high yields, and support soil-centric green revolutions. Achieving landscape-level mosaics of natural biotic populations and fine-grained crop diversification is key to restoring biodiversity lost during the Green Revolution era. Through this review, we discuss the benefits of crop diversification in promoting natural ecological processes. These outcomes arise from the complex interplay between structural elements—such as governance, cultural norms, and resource availability—and individual or collective agency, including priorities, collaboration, and strategic choices. This dynamic relationship shapes the pathways of crop diversification, influencing its role in promoting natural ecological processes and its adoption in diverse agricultural contexts. When individuals and communities collaborate through robust networks and well-supported institutions, the dissemination of sustainable practices across farms and landscapes becomes significantly more effective. This collective action, fueled by shared knowledge, innovation, and access to resources, enhances the capacity to integrate ecological principles that build resilient and sustainable agroecosystems. So, crop diversification practices contribute to a “win–win” outcome by supporting yield stability, enhancing environmental adaptability, and promoting long-term profitability. The upscaling adoption of diversification practices is crucial for conserving biodiversity, mitigating climate change, and transforming food systems on local to global scales. This needs to be urgently acknowledged by scientist to enable better governance and evidence-based policymaking for an agricultural paradigm shift rooted in natural ecologies.